Fracture of the coronoid and pterygoid processes by firearms: case report - Oliveira,David Moraes de (2007)
A rare case of fracture of the coronoid and the pterygoid process caused by firearms is described. A 28-year-old male was hit by a bullet in the face, resulting in restricted mouth opening, difficulty in chewing and pain when opening the mouth. Clinical examination revealed a perforating wound in the right parotid region and a similar wound on the left side of the same region. A CT scan showed comminuted fracture of the left coronoid process and bilateral comminuted fracture of the pterygoid processes. Treatment was conservative, speech therapy was conducted and it was successful. Details of the clinical signs, radiology (3D-CT scan), treatment and follow-up are presented.